Circular economy adoption by SMEs in the emerging markets: Towards a multilevel conceptual framework - Malik, Ashish; Sharma, Piyush; Vinu, Ajayan; Karakoti, Ajay; Kaur, Kamalpreet; Gujral, Harpreet Singh; Munjal, Surender; Laker, Benjamin (Elsevier, 2021)
Adding to the growing literature on circular economy (CE) and employing the theoretical lens of change management, this research explores SMEs’ challenges in the emerging markets context of India for adopting CE practices. We use a multi-case qualitative design, interviewing senior leaders and owners of Indian SMEs, CE intermediaries and two large firms on the nature and extent of critical barriers and enablers of CE adoption. Including CE market intermediaries, sustainability and CE managers of large organizations, who are required to educate and incentivize CE adoption of their SME value chain members, we analyze the barriers and opportunities from both sides of the coin. We develop a multilevel theoretical framework grounded in CE and change management literature, which presents the nature and extent of CE activities, barriers and contextual enablers of SMEs’ adoption of CE in emerging markets. Implications for policy, theory and practice are also discussed.